Tingkat Persepsi Petani Terhadap Budidaya Tanaman Kopi Arabika (Coffea Arabica) Di Desa Kutarayat Kabupaten Karo - Warly Putri, Sri Shinta; Safitri, Sri Ariani (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2025)
Coffee is one of the plantation commodities with high economic value among other plantation crops and plays an important role as a source of national foreign exchange. This study aims to determine the level of farmers’ perceptions toward Arabica coffee cultivation in Kutarayat Village, Naman Teran Subdistrict, Karo Regency. The research location was selected purposively based on specific considerations. A total of 35 farmers were selected as respondents. The research employed both primary and secondary data. Data analysis was conducted using a descriptive quantitative method. To assess the level of farmers' perceptions of Arabica coffee cultivation, a Likert scale was used, in which the total score obtained was divided by the maximum possible score and multiplied by 100%. Farmers’ perceptions of Arabica coffee cultivation were categorized into three aspects: economic, technical, and social. The results showed that the level of farmers' perceptions of Arabica coffee cultivation was relatively high, particularly in terms of technical perception (88.57%), economic perception (77.90%), and social perception (68.57%), with an overall average score of 78.35%, categorized as Good.